2022
DOI: 10.1186/s13099-022-00518-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proton pump inhibitors in infants with esophageal atresia on the gut microbiome: a pilot cohort

Abstract: Background The effects of proton-pump inhibitors (PPIs) on the infant microbiome remain unclear. Swedish pilot cohort study to assess the longitudinal effect of long-term PPI on the infant gut microbiome, including ten newborn infants operated for esophageal atresia exposed to PPIs (mean 57 weeks), compared to healthy one-year-old controls. All children were born vaginally and were otherwise healthy. Within- and between sample diversity of the fecal microbiome was assessed using untargeted whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…In addition, the initial gut colonization is highly influenced by the maternal microbiome (vaginal and fecal) [6,7], and the maternal microbiome seems to play an important role in the onset of pregnancy complications [8][9][10]. In turn, PPI use has been associated with important changes in the gut microbiome that appear to be more prominent than those related to antibiotic use [11], also in infants as shown in our small pilot study [12]. The Food and Drug Administration (FDA) used to classify (up till 2015) most PPIs as category B drugs ("No risk in animal studies"), except for omeprazole which was categorized as type C ("Risk cannot be ruled out") [13,14].…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…In addition, the initial gut colonization is highly influenced by the maternal microbiome (vaginal and fecal) [6,7], and the maternal microbiome seems to play an important role in the onset of pregnancy complications [8][9][10]. In turn, PPI use has been associated with important changes in the gut microbiome that appear to be more prominent than those related to antibiotic use [11], also in infants as shown in our small pilot study [12]. The Food and Drug Administration (FDA) used to classify (up till 2015) most PPIs as category B drugs ("No risk in animal studies"), except for omeprazole which was categorized as type C ("Risk cannot be ruled out") [13,14].…”
Section: Introductionmentioning
confidence: 59%
“…To our knowledge, there are no randomized clinical trials investigating the safety of maternal PPI use, regarding maternal and neonatal adverse events [2,45,46]. We also question if it is still ethically defendable to conduct these on PPI use during pregnancy with the accumulating safety concerns based on association studies, and our increasing understanding of drug interactions and the microbiome [2,5,12,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…24 Similarly, prolonged PPI use in infants is associated with changes in the evenness and diversity of bacteria. 25 Acid suppressants have also been demonstrated to increase sensitization to orally digested proteins. 26 In a recent meta-analysis, 10 childhood acid suppressant use has been associated with elevated risk of asthma, atopic dermatitis, and allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…In an assessment before and after PPI treatment of the fecal microbiome, the relative abundance of Lactobillus and Stentrophomonas species decreased with PPI treatment . Similarly, prolonged PPI use in infants is associated with changes in the evenness and diversity of bacteria . Acid suppressants have also been demonstrated to increase sensitization to orally digested proteins .…”
Section: Discussionmentioning
confidence: 99%
“…23 In a recent pilot study assessing the effect of PPI's on infants with EA, it was shown that longer duration of PPI use was associated with lower Shannon diversity. 24 Children with EA had a significant difference in bacterial communities compared to HC based on beta diversity analysis. In the current study, the order Lactobacillales was enriched in children with EA compared to HC.…”
Section: Firmicutes ↑Bacilli ↑Lactobacillalesmentioning
confidence: 95%